The STEAM Approach in Brazil: gaps and implications for Natural Sciences, Humanities, and Mathematics Education - Munhoz, Gabriel Victor (2024)
High school students encounter difficulties understanding the contents of natural sciences, humanities, and mathematics taught in schools. Numerous studies link disconnected teaching and demotivating methodologies as causes for this issue in the literature. In this perspective, the National Common Curricular Base (hereby BNCC) and the Curriculum Reference Document for Mato Grosso (hereby DRC-MT) propose changes in teaching and learning using active methodologies and the STEAM approach. The aim of this article was to identify key gaps in STEAM approach knowledge in Brazil, as well as its implications for teaching natural sciences and mathematics, enhancing understanding of its application in the country. Based on this, an analysis was conducted on publication locations and applied education levels. This qualitative, interpretive research is part of a bibliographic study, demonstrating a significant increase in production in recent years.